Inhibition of high glucose-induced cardiac fibroblast activation: an effective treatment for diabetic cardiomyopathy using Chinese herbal medicine - Bin Wan; Jing Hu; Yue Luo; Yutong Han; Yaowen Zhang; Qinchuan Huang; Yulin Leng; Chunguang Xie; Chunguang Xie (Frontiers in Pharmacology)
Diabetic cardiomyopathy (DCM) is one of the common diabetic microangiopathy in clinical practice. In the early stage of the disease, there are no obvious clinical symptoms. In the middle and late stages, MF, arrhythmia, and even heart failure may occur, affecting the life and health of patients. MF, as one of the pathological features of DCM at the end stage, is the key factor of poor prognosis leading to ventricular wall stiffness and heart failure, which affects the clinical process and outcome of patients. The development of MF in a high glucose environment involves multiple complex fibrogenic pathways that work together to activate fibroblasts, thereby promoting MF. Indeed, aberrant activation of cardiac fibroblasts (CFs) is a key factor in MF. Therefore, inhibiting the activation of CFs may become a new strategy for the treatment of DCM. Previous studies have shown that Chinese herbal medicine (CHM) has potential in the treatment of DCM. In this review, we first introduced the physiology and function of CFs and discussed the conditions for the pathological activation of CFs in the process of diabetes, and then systematically summarized the effects of CHM on the activation of CFs by controlling the production of advanced glycosylation end products, oxidative stress and inflammation. This review will illustrate the potential of CHM to inhibit the activation of CFs and provide new ideas for the treatment of DCM.